Algorithms for Sensor and Ad Hoc Networks: Advanced Lectures - Wagner, Dorothea; Wattenhofer, Roger (Lecture Notes in Computer Science, 2007)
Wireless ad hoc and sensor networks have gained an incredible research momentum. Computer scientists and engineers of all flavors are embracing the area. Sensor networks have been adopted by researchers from many different fields, ranging from hardware technology to operating systems, from antenna design to databases, from information theory to networking, from graph theory to computational geometry. The purpose of this monograph - outcome of a GI-Dagstuhl Seminar held in Dagstuhl Castle in November 2005 - is to give a first overview of algorithmic results on wireless ad hoc and sensor networks. Its focus is on algorithms and protocols that allow for an analysis of their efficiency and efficacy. Many chapters deal with distributed algorithms, in particular local and localized algorithms. Importance is attached to topics combining both interesting aspects of wireless networks and attractive algorithmic methods. Each chapter provides a survey of some part of the field, whilst selected results are described in more detail. The structure and content of the book would make it a suitable basis for an advanced course.